Pregnancy loss in anamnesis: short and long term consequences for women's health - Siusiuka, V. H.; Belenichev, I. F.; Deinichenko, O. V.; Soloviova, N.; Сюсюка, Володимир Григорович; Бєленічев, Ігор Федорович; Дейніченко, Олена Валеріївна (Valencia : International Center of Scientific Research, 2024)
Resume. The article presents an analysis of modern research on the relationship between pregnancy loss (natural or induced) and short-/long-term consequences for a woman's health. The presence of a case of pregnancy loss in the anamnesis negatively affects the reproductive function of a woman in the future, affects the course and outcome of the next pregnancy. However, reproductive risk factors are not limited to the obstetric period. The association between spontaneous abortion and cardiovascular disease may reflect shared mechanisms and is considered an early marker of future risk to women's health, including premature death. Therefore, future efforts should focus on increasing follow-up of mothers after delivery, increasing awareness of risk factors, and evidence-based prevention strategies for this cohort of women.